An Eastern Heart in a Western Chest: Annemarie Schimmel’s Spiritual Journey into Iqbaliyat - Prof. Dr. Abdul Rauf Rafiqui (Journal of Religion and Society, 2025)
Annemarie Schimmel balanced a European sense of reason with an Eastern ability to feel. She became the necessary bridge between Germanistik and Islam. She unlocked the "Western Chest" of philology and meticulous scholarship, and opened her "Eastern Heart" to embrace her subjects on their own terms. She did not merely observe; she breathed their air. Annemarie Schimmel's greatest gift may have been transmitting Muhammad Iqbal's message to the world. She created a new method of motif-history to interpret Iqbal's symbols of the Falcon and the Tulip. Thanks to her, Iqbal now stands on the world stage with Goethe and Dante. In the end, Annemarie Schimmel showed us how to love. Through her life we know that East and West need not be competing sides of conflict, but complementary forces that can unite through empathy. Keywords: Eastern Heart, Western Chest, Annemarie Schimmel, Spiritual Journey, Iqbaliyat.